2012
DOI: 10.18352/lq.8054
|View full text |Cite
|
Sign up to set email alerts
|

How to Mobilize your Library at Low Cost

Abstract: The W3C defines the mobile web as a web in which users are able to access information from any location, regardless of the type of device used. In recent years, Internet access from mobile devices has grown considerably. This is due to many factors such as technological improvements of these devices, faster data transmission and lower connection costs. This new context has led to the creation of various mobile web tools which offer a variety of features, such as adaptability of web websites, use of QR codes (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…More people are using mobile devices, such as smartphones and tablets, to browse and use resources on the internet. Abarca Villoldo et al (2012) indicated that improvements in mobile device technology, faster transmission speeds and lower connection costs have facilitated the increase in smartphone users. Smartphones have become major devices for many people to access the internet (Pew Research Center, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More people are using mobile devices, such as smartphones and tablets, to browse and use resources on the internet. Abarca Villoldo et al (2012) indicated that improvements in mobile device technology, faster transmission speeds and lower connection costs have facilitated the increase in smartphone users. Smartphones have become major devices for many people to access the internet (Pew Research Center, 2018).…”
Section: Introductionmentioning
confidence: 99%